Teori Maslahat Dalam Perceraian : Studi Pasca Berlakunya UU No. 1 Tahun 1974 Dan Kompilasi Hukum Islam - Jamaluddin Jamaluddin (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2012)
Divorce is something that is not expected to occur in a marriage, because the purpose of marriage is to establish a happy and eternal family. However, not all marriages can be a happy marriage and last forever. When the conflict happens between husband and wife and there is no more peaceful solution, the law gives alterative to a divorce, so the husband and wife can get out of the crisis. Anyway, divorce should not happen too easily, and according to the hopes of the couple. In the Law Number 1 in 1974 concerning Marriage and Compilation of Islamic law which one of the purposes is to give welfare, if the divorce is chosen as alternative solution to the family crisis.